2011
DOI: 10.1007/s00595-011-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

A canine model of multiple organ dysfunction following acute type-A aortic dissection

Abstract: A novel canine model of acute Stanford type-A aortic dissection has been developed, which showed multiple organ dysfunction that mimicked the clinically relevant features observed in man. This aortic dissection model is unique, and may further improve our understanding of the underlying pathogenesis of aortic dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…They were fed in the West China Clinical Medical College of Sichuan University/The Experimental Animal Center of West China Hospital, following the regulations for experimental animal welfare. Canines were randomly divided into sham operation(SO) and dissection groups, and were subjected to median thoracotomy alone, or sternotomy with ascending aorta clamping and an aortic dissection surgical procedure, respectively,as previously reported [ 2 ]. Briefly, after routine sterile preparation and draping, a median sternotomy was performed to expose the ascending aorta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were fed in the West China Clinical Medical College of Sichuan University/The Experimental Animal Center of West China Hospital, following the regulations for experimental animal welfare. Canines were randomly divided into sham operation(SO) and dissection groups, and were subjected to median thoracotomy alone, or sternotomy with ascending aorta clamping and an aortic dissection surgical procedure, respectively,as previously reported [ 2 ]. Briefly, after routine sterile preparation and draping, a median sternotomy was performed to expose the ascending aorta.…”
Section: Methodsmentioning
confidence: 99%
“…The 24-h mortality rate is greater than 35 %, and more than half of patients die within 48 h [ 1 ]. Previous studies revealed inflammatory changes in the aortic wall and plasma during the course of aortic dissection [ 2 ]. However, an effective therapeutic strategy targeting inflammation-associated aortic dissection has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both the genetically determined loss of function and the “paradoxical” augment in the downstream TGF- β signalling pathway might be important for TAA development [ 42 ]. Furthermore, vascular remodelling, characterizing thoracic aneurysm, seems prevalently to be the result not only of TGF- β pathways but also of upregulation of multiple cytokines, including interleukin-10 (IL-10) [ 43 ], an anti-inflammatory cytokine able to modulate the activity of TGF- β pathway, interleukin-6 (IL-6), interleukin-8 (IL-8), tumour necrosis factor- (TNF-) α , and monocyte chemoattractant protein-1 [ 44 46 ]. On the other hand, interesting studies revealed that circulating levels of interferon- γ , interferon- γ -induced chemokines, interferon-inducible T-cell alpha chemoattractant, interferon-inducible protein-10, and monokine induced by interferon gamma are all increased in patients affected by TAAs, even if the levels of these chemokines do not correlate with the size of the aneurysms [ 47 ].…”
Section: Role Of Cytokines In Taa Pathogenesismentioning
confidence: 99%
“…18 Development of new stent-grafts for use in the ascending aorta and aortic root will require a true-to-life model, ideally pressurized, where acute changes in aortic geometry following type A dissection have to be considered for device designs. Li and colleagues 19 surgically induced aortic dissection in a canine model to study multiple-organ dysfunction. Okuno and colleagues 20 developed a promising aortic dissection model.…”
Section: Discussionmentioning
confidence: 99%